Case Report: Positive Mycoplasma pneumoniae IgM does not necessarily indicate acute infection: two case studies - Wang, Hao; Liu, Xiaoying; Wu, Yabin; Cao, Xin; Liu, Jie; Li, Wei (Frontiers in Pediatrics, 2025)
BackgroundWe aimed to explore the duration of IgM antibodies against Mycoplasma pneumoniae.MethodsData from two children who consistently tested positive for M. pneumoniae IgM antibodies were retrospectively analyzed. Moreover, we examined the etiological data and drug use of these cases. Serologic testing using the colloidal gold method, direct chemiluminescence technique, and specific immune agglutination test were utilized. Quantitative PCR was used to detect M. pneumoniae in bronchoalveolar lavage fluid and antigen tests and nucleic acid detection were conducted for other respiratory pathogens.ResultsThe serological positivity of M. pneumoniae IgM antibody persisted for nearly ten months in one child and more than fifteen months in the other child. Furthermore, the persistently positive M. pneumoniae IgM antibody tests led to the inappropriate use of macrolides during multiple hospitalizations.ConclusionsIgM antibodies against M. pneumoniae may remain positive for an extended duration. Therefore, a positive Mycoplasma pneumoniae IgM test does not necessarily indicate the presence of an acute infection.